PENGUATAN IMAN ANAK MELALUI KEGIATAN SEKAMI (SERIKAT KEPAUSAN ANAK MISIONER) DI PAROKI SAN JUAN LEBAO - Servina Retno Anna Lewar; Marta Fila Delvia Lauley; Maria Yunita Corebima (JOURNAL OF COMMUNITY DEDICATION, 2026)
Children are an important part of the Church because they are the future generation who will continue the mission and life of faith in the Church. One of the Church's efforts to nurture children's faith is through the activities of the Missionary Childhood Association (SEKAMI). However, the participation and understanding of children regarding faith formation activities are still faced with various challenges, such as the influence of technology, lack of parental support, and limited faith development programs. This community service activity aims to strengthen children's faith through SEKAMI activities at San Juan Lebao Parish. The method used is a descriptive qualitative approach through observation, interviews, faith formation activities, and mentoring. The results show that SEKAMI activities help children deepen their faith, increase participation in church activities, foster missionary spirit, and build positive Christian character. Therefore, continuous faith formation through SEKAMI is important in supporting children's spiritual growth.